Activation of the AMP-Activated Protein Kinase by Eicosapentaenoic Acid (EPA, 20:5 n-3) Improves Endothelial Function In Vivo - Wu, Yong; Zhang, Cheng; Dong, Yunzhou; Wang, Shuangxi; Song, Ping; Viollet, Benoit; Zou, Ming-Hui (PLOS ONE, 2012)
The aim of the present study was to test the hypothesis that the cardiovascular-protective effects of eicosapentaenoic acid (EPA) may be due, in part, to its ability to stimulate the AMP-activated protein kinase (AMPK)-induced endothelial nitric oxide synthase (eNOS) activation. The role of AMPK in EPA-induced eNOS phosphorylation was investigated in bovine aortic endothelial cells (BAEC), in mice deficient of either AMPKα1 or AMPKα2, in eNOS knockout (KO) mice, or in Apo-E/AMPKα1 dual KO mice. EPA-treatment of BAEC increased both AMPK-Thr172 phosphorylation and AMPK activity, which was accompanied by increased eNOS phosphorylation, NO release, and upregulation of mitochondrial uncoupling protein-2 (UCP-2). Pharmacologic or genetic inhibition of AMPK abolished EPA-enhanced NO release and eNOS phosphorylation in HUVEC. This effect of EPA was absent in the aortas isolated from either eNOS KO mice or AMPKα1 KO mice fed a high-fat, high-cholesterol (HFHC) diet. EPA via upregulation of UCP-2 activates AMPKα1 resulting in increased eNOS phosphorylation and consequent improvement of endothelial function in vivo.